Comparative evaluation of the nutritive values of dried ryegrass and clover / Mohd Nizar Khairuddin … [et al.] - Khairuddin, Mohd Nizar; Peter, Lane; Syahlan, Syahrizan; Zulkefli, Farahida (2012)
In pasture production ryegrass and clover was the main source to feed livestock such as cattle, sheep and goats especially to fulfil the requirement in providing adequate amounts of nutrients that the animal need. This experiment was conducted to see which source has the highest nutritive values and which source is the best to feed livestock. There were six nutritive values that were important and be calculated throughout this experiment. The nutritive values that being calculated are valued on dry matter, crude protein, neutral detergent fibre (NDF), acid detergent fibre (ADF), ether extract (EE) and ash. The feeder supply used in this experiment is dried ryegrass and clover. The experiment was based on the ruminant requirement within limited feeds sources during winter season. Dries ryegrass has a higher NDF and ADF, a good percentage of EE and CP can be given to ruminant's especially growing cattle. It was important in order to increase an optimum metabolism and improve rate growth. Furthermore, this experiment also discusses about the clover which has a lower NDF and ADF, but high in fats and crude protein. However, it was more suitable for lactating cows which depend on more energy and other minerals were required for the production of milk. Nevertheless, increase the optimum requirement of the cattle depending on their stages of growth and also their weight for better production.